A next step in exoplanetology: exo-moons. Issue 2 (April 2015) - Schneider, J.; Lainey, V.; Cabrera, J.
Abstract The interest of exo-moons for Astrobiology is that they widen significantly the potential niches of exolife. In this paper, after a review of standard detection methods, we investigate new ways to characterize exo-moons and to use them to characterize their home planetary system.